PEDAGOGICAL CONDITIONS FOR THE FORMATION OF GRAPHIC CULTURE OF SCHOOL STUDENTS IN THE PROCESS OF USING COMPUTER TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the study is the scientific and experimental identification of a complex of effective pedagogical conditions for the formation of the graphic culture of school students in the process of using computer technologies. In the article, based on the analysis of the structure of graphic culture in the system of the general culture of the personality of a student of the XXI century, as well as identifying the features of the use of computer technologies in modern school education, the effectiveness of creating pedagogical conditions for the formation of the graphic culture of school students is theoretically and experimentally substantiated: the use of a complex of program-methodological and pedagogical teaching aids using computer technology, the implementation of an active learning model in the organization of educational activities and the interaction of the teacher and students in the classroom. The article describes an empirical study of the conditions for the formation of the graphic culture of school students in sketching lessons: the diagnosed parameters are determined, a comprehensive test of the level of graphic culture in secondary school students is carried out, an assessment of the effectiveness of the influence of a complex of pedagogical learning conditions on the formation of the graphic culture of students is given. The experiment revealed the need to create special pedagogical conditions that form the basis for the development and implementation of the elective course program “Technical Sketching Using CAD”.